2019
DOI: 10.1111/aji.13128
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell–induced immunopathology in recurrent pregnancy losses

Abstract: Problem Mast cells (MC) have been known to play an important role in inflammation and angiogenesis by secreting numerous mediators, such as proteases, gelatinases, and proteoglycans. Three different MC subtypes were found in the endometrial layers of the uterus. In this study, we aim to investigate the role of endometrial MCs in recurrent pregnancy losses (RPL). Method of study Endometrial biopsy was performed 5‐7 days post‐ovulation (implantation window) in women with a history of two or more RPL (n = 46) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 90 publications
0
9
0
Order By: Relevance
“…We anticipate that future studies will contribute to an increasing understanding of the role of single MC mediators for pregnancy success. It is suggested that increased numbers or exacerbated activation of MCs is associated with human pregnancy pathologies like recurrent pregnancy losses (122) and PE (123,124). The mechanisms underlying this phenomenon are not explored.…”
Section: Uterine Mast Cells (Umcs)mentioning
confidence: 99%
“…We anticipate that future studies will contribute to an increasing understanding of the role of single MC mediators for pregnancy success. It is suggested that increased numbers or exacerbated activation of MCs is associated with human pregnancy pathologies like recurrent pregnancy losses (122) and PE (123,124). The mechanisms underlying this phenomenon are not explored.…”
Section: Uterine Mast Cells (Umcs)mentioning
confidence: 99%
“…MCs are found in the endometrium as round or ovoid granular cells more often, whereas elongated shapes of them abound in the basal layer and endometrium/myometrium junction . Leo et al investigated the subtypes of MCs during stages of the menstrual cycle.…”
Section: Mast Cells and Fertility In Femalesmentioning
confidence: 99%
“…Accumulation of MCs throughout all layers of the endometrium has been reported in women with a history of pregnancy loss. MC activation in these women resulted in higher levels of SCF, tryptase, heparin sulfate, and MMP‐2 . To elucidate the role of MCs in abortion, Woidack et al decided to perform the adoptive transfer of Tregs to support the MC‐mediated angiogenesis in abortion‐prone mice which have lower MC numbers in their uterus tissue.…”
Section: Mast Cells and Pregnancy Lossesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mast cells are resident immunological cells found abundantly in tissues such as skin, endometrium and placenta that have prominent roles in immunologic reactions [10][11][12][13]. Their presence and prevalence in these tissues, along with their proximity to blood vessels, predispose these cells to be among the first immune cells that can be infected by ZIKV after a mosquito bite penetrates the skin.…”
Section: Introductionmentioning
confidence: 99%